A Comparison of Bipolar and Unipolar Rating Scales in Student Evaluations of Teaching - Dobrovoljc, Nika; Jerebic, Janja; Brezavšček, Alenka; Kajzer, Špela (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
This paper empirically examines the effects of unipolar and bipolar rating scales on the outcomes of student evaluations of teaching. In a pilot study, two comparable groups of students evaluated identical items using different rating scales. Analyses of score distributions, mean values, and top-category response shares indicate that the use of a bipolar scale leads to a statistically significantly higher concentration of responses at the upper end of the scale for most items, reflecting a more pronounced ceiling effect. The findings support theoretical expectations regarding the influence of scale polarity on response behaviour and demonstrate that rating format selection affects score variability and result interpretability. The paper discusses the methodological implications of rating scale choice and contributes to the ongoing debate on appropriate evaluation practices in higher education.